The first encounter - Bely, Andrey, 1880-1934 (Princeton legacy library., 1979)
First published in Russian in 1921 and never translated, Andrey Bely's long narrative poem-considered to be one of the great achievements of Russian Modernism-is translated to English here. A poet, critic, philosopher, and novelist, Bely was a leading figure among the Russian Symbolists, and The First Encounter is thought to be his greatest work in verse. The poem is autobiographical and reflects turn of-the-century Moscow with its mixture of entrenched positivism and new spiritualistic trends, cultural variety and the upheaval of the time. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.